2020
DOI: 10.1007/s10067-020-05494-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of COVID-19 in patients with rheumatic disease: is prior health education more important than shielding advice during the pandemic?

Abstract: The COVID-19 pandemic has led to major changes in clinical practice on a global scale in order to protect patients. This includes the identification of vulnerable patients who should “shield” in order to reduce the likelihood of contracting SARS-CoV2. We used national specialty guidance and an adapted screening tool to risk stratify patients identified from our prescribing and monitoring databases, and identify those needing to shield (score ≥ 3) using information from departmental letters, online general prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Initially, shielding, or strict quarantine and minimizing non‐essential contact even with other household members, was recommended for certain high‐risk RMD patients 13 . However, shielding may even be less important than self‐education and adherence to general preventive measures 14 . RMD patients should thus be advised to follow locally stipulated guidance for transmission prevention as advised for the general population.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, shielding, or strict quarantine and minimizing non‐essential contact even with other household members, was recommended for certain high‐risk RMD patients 13 . However, shielding may even be less important than self‐education and adherence to general preventive measures 14 . RMD patients should thus be advised to follow locally stipulated guidance for transmission prevention as advised for the general population.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, they have led to some changes in an "unfavorable" direction, generally increasing the risk of infections. Nevertheless, numerous high-quality studies have already found that the risk of contracting SARS-CoV-2 and poor COVID-19 outcomes of patients with the most common AIID is similar to the general population [15,16]. In the case of immunosuppression, the response to some vaccines and the efficacy resulting in immunogenicity, however, has become unpredictable, especially in the case of B cell depleting therapies [17].…”
Section: Covid-19 and Patients With Autoimmune Inflammatory Diseasesmentioning
confidence: 99%
“…Although preliminary data showed that AIIDs themselves did not pose an increased risk of SARS-CoV-2 infection and severe disease [15,16], there is a complexity of disease-disease and drug-disease interactions characteristic of AIIDs that need special consideration. AIID-induced organ damage, coexisting chronic cardiovascular, metabolic, and respiratory comorbidities, predisposition to bacterial infections, B cell depletion therapies, and the use of high-dose glucocorticoids could increase the risk of poor outcome [19].…”
Section: Covid-19 and Patients With Autoimmune Inflammatory Diseasesmentioning
confidence: 99%
“…Patients with systemic autoimmune rheumatic disease (AIRD) are a vulnerable group for SARS Cov-2 infection [3][4][5]. The heterogeneous nature of AIRD and treatment with various immunomodulators can lead to an immunocompromised state.…”
Section: Introductionmentioning
confidence: 99%